A model to adjust the falling weight deflections due to temperature variations - Pais, Jorge C. (2017)
The evaluation of the bearing capacity of the pavement that is used to assess the stiffness modulus of its layers and is usually carried out by the measurement of the pavement deflections due to the application of a known load through a falling weight deflectometer. These measurements are influenced by the pavement temperature and the obtained stiffness moduli can only be compared if they correspond to the same temperature. Thus, this work develops a model to adjust the pavement deflections to a reference temperature based on the characteristics of the pavement. The development of the work is divided into four parts: i) a laboratory evaluation of the stiffness modulus of asphalt mixes at different temperatures and the proposal of a model for the stiffness modulus as function of the temperature; ii) assessment of the pavement deflections for different testing conditions; iii) development of a deterministic model for the adjustment of the pavement deflection; and iv) validation of the model.